Metronomic chemotherapy for paediatric extracranial solid tumours: a systematic review and meta-analysis of randomised clinical trials - Frank Peinemann; Marc Hoemberg (BMJ Open)
Background Metronomic chemotherapy (‘less is more, regularly’) could be an alternative to the maximum tolerated dose (‘the more, the better’) in the chemotherapeutic cancer treatment of high-risk malignant solid extracranial tumours in children or young adults.Objective To evaluate the efficacy of metronomic chemotherapy compared with placebo or stop treatment in paediatric patients with extracranial malignant solid tumours.Methods We searched the databases MEDLINE and CENTRAL on 8 September 2023 and included randomised clinical trials (RCTs). Primary outcome was overall survival, and the main outcome measure was the HR.Results We identified three RCTs with parallel assignment and intention-to-treat analyses of data from 775 people. The studies primarily reported on participants with rhabdomyosarcoma, neuroblastoma and osteosarcoma. The HR favoured the metronomic chemotherapy group (0.75 (95% CI 0.56 to 0.98)).Conclusions The evidence base is compatible with a favourable effect of metronomic chemotherapy on children and young adults with high-risk extracranial malignant solid tumours, especially other than bone tumours, when compared with placebo or stop treatment. Statistical heterogeneity is low while clinical heterogeneity is substantial. Thus, the results must be interpreted with caution and applicability of the results is limited. Future RCTs could provide more data on individual tumour entities and subsequently add information on tumour-specific responses.PROSPERO registration number CRD42023457195.